Clinicoradiological correlation of type 1 tympanoplasty in wet and dry ears - Sachdeva, Sarthak; Vaid, Divya; Vaid, Lakshmi; Bhatt, Shuchi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Chronic otitis media patients can present with a dry or wet ears (which means those ears which have a mild mucoid discharge and are negative on culture). Preoperative HRCT scans done in these patients show either a normal or an opacified mastoid cavity. This creates a dilemma in the mind of an otologist as whether doing a tympanoplasty in a patient with an active mucoid ear discharge would be beneficial or not. The goal of this study is to compare results of type 1 tympanoplasty in wet and dry mucosal COM ears and correlate between preoperative CT findings and postoperative outcomes. Methods: A comparative study was done where a total of 30 wet and 30 dry ears respectively were included based on a preset clinical criterion. After a detailed history, otoscopic examination, pure tone audiometry (PTA) and a HRCT scan of temporal bone, all patients underwent type 1 tympanoplasty followed by PTA assessment 2 months postoperatively. Results: The graft uptake rates and hearing outcomes after surgery were found to be similar in both wet and dry ears. Also, the graft uptake rates in patients with opaque mastoids were similar to those with normal mastoids on HRCT scans. Conclusions: This study concludes that success of type 1 tympanoplasty surgery is not adversely affected by the presence of mucoid discharge at the time of surgery. For achieving good surgical success, meticulous graft placement is more important rather than status of the operated ear.